Explicating the influence of artificial intelligence (AI) literacy on employee performance - Loke, Li Ying (2024)
Artificial Intelligence (AI) technology's swift incorporation into the workplace has made AI literacy a crucial skill for workers in several sectors. This study examines how employee performance is affected by AI literacy, with a particular emphasis on four important areas: awareness, usage, evaluation, and ethics. The association between AI literacy and performance results is not well-established, even though AI is often considered in terms of its potential. By investigating the various ways in which AI literacy enhances employee performance, the study closes that knowledge gap and offers insightful information to both academics and businesses. The study utilised a quantitative causal research methodology and collected data from 219 employees across various sectors in Malaysia through the administration of an online survey. The survey evaluated the respondents' perceived influence on employee performance and their level of AI literacy. Partial Least Squares Structural Equation Modelling (PLSSEM) was used for data analysis to assess the constructs' validity and reliability as well as to validate the suggested relationships. AI literacy is positively influencing employee performance. Employees who actively used and were more aware of AI technologies performed better, which emphasises the need to improve these aspects of AI literacy through focused training programs. In addition, the study emphasises the significance of ethical considerations and careful assessment of AI literacy to optimise their benefits in the workplace. This study adds to the body of knowledge in academia and in realworld applications by providing a thorough framework for comprehending the relationship between AI literacy and employee performance. The knowledge acquired may assist companies in creating AI strategies and employee development plans that are more successful, and it can also advise schools on how to better prepare students for work settings that are driven by AI.